Energy poverty and retirement income sources in Australia - Fry, Jane; Farrell, Lisa; Temple, Jeromey (My University, 2022)
In many countries population ageing will increase the share of retirees in the coming years. Energy poverty is a particular problem for older people (due to fixed and often relatively low incomes and the need for additional energy due to underlying health conditions). This can have cost implications for the healthcare sector if the health of older people deteriorates due to energy poverty. The burden of population ageing and the increasing dependency ratio has meant the government is moving towards individuals funding their own retirement via compulsory superannuation schemes. Our study is based in Australia where there is a difference in retirement income sources between publicly funded Age Pensioners, Part-pensioners and Self-Funded Retirees leading to differences in energy poverty beyond income effects. Using 15 annual waves of the HILDA survey from 2005 to 2019, this study investigates drivers of energy poverty inequalities among retirees. Our main finding is that Age Pensioners are the worst off and Self-Funded Retirees the best off on a Low Income–High Cost measure of energy poverty and on a subjective indicator of inability to heat the home. Therefore, not all retirees have the same probability of experiencing energy poverty. However, wealth, assets, social connections and good health are significant mediators that soften the impact of subjective concerns regarding energy bills for retirees. Government-funded pensions are a safety net and need to be sufficient in times of energy price inflation. Moreover, we need to reduce the gap between state-funded pensions and self-funding arrangements to ensure equity in elderly populations.
Energy Economics
Keywords: Ageing; Health and wellbeing; Income, wealth and finances